2021
DOI: 10.1039/d1cc02786g
|View full text |Cite
|
Sign up to set email alerts
|

Varying the hydrophobic spacer to influence multicomponent gelation

Abstract: Mixing low molecular weight gelators (LMWGs) shows promise as a means of preparing innovative materials with exciting properties. Here, we investigate the effect of increasing hydrophobic chain length on the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Here we show that combination of a dipeptide gelator (compound 1 ) with non‐gelling amphiphiles (compounds 2 – 6 ) can produce gels at low pH whilst the properties of the multicomponent systems are significantly dependent on the hydrophobicity of the non‐gelling component (Figure 1). We have previously shown that Fmoc‐amphiphiles with short alkyl chain (compounds 2 – 4 ) primarily undergo self‐sorting with 1 [9] . Here, we find that, when the amphiphiles are more hydrophobic ( 5 and 6 ), gel formation is driven by co‐assembly.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Here we show that combination of a dipeptide gelator (compound 1 ) with non‐gelling amphiphiles (compounds 2 – 6 ) can produce gels at low pH whilst the properties of the multicomponent systems are significantly dependent on the hydrophobicity of the non‐gelling component (Figure 1). We have previously shown that Fmoc‐amphiphiles with short alkyl chain (compounds 2 – 4 ) primarily undergo self‐sorting with 1 [9] . Here, we find that, when the amphiphiles are more hydrophobic ( 5 and 6 ), gel formation is driven by co‐assembly.…”
Section: Introductionsupporting
confidence: 54%
“…Dipeptide 1 forms a self‐supported, invertible gel almost instantly (within few seconds) in DMSO/H 2 O (20/80, v/v) (Figure 1, bottom) [9] . The pH of the gel is around 4.3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials. The 1ThNapFF gelator was synthesized as described previously [ 38 ]. Urease (U4002-100KU, Jack Beans, 100,000 units/g solid) and urea (ultrapure 99%) were purchased from Alfa Aesar.…”
Section: Methodsmentioning
confidence: 99%
“…The self-assembly of peptides is also partially controlled by interactions between hydrophobic amino acid residues, such as associative phenylalanine-phenylalanine (FÀ F) interactions, which are commonly observed in supramolecular peptide hydrogels. [69][70][71] In addition, enzymes can also be used as a stimulus to trigger the self-(dis)assembly in supramolecular hydrogels, and the inherent biocompatibility of peptide-based gels makes them ideal targets for enzymatic cleavage. [72] Moreover, the mild reaction conditions required for enzymatic reactions, as well as the homogeneity of the resulting hydrogels are additional advantages of peptide hydrogels.…”
Section: Small Gelators: Peptidesmentioning
confidence: 99%